'Am I not beautiful?': cultural identity and the process of co-authorship. Issue 2 (3rd April 2019) - Kelman, Dave
ABSTRACT: This case study of a community youth theatre project interweaves reflective descriptions of practice, data excerpts and analysis to examine young people's exploration of cultural identity through theatre in a regional city in Australia. The process undertaken to create this work is theorised in relation to concepts of cultural difference and cultural diversity, cultural representation and local identity. The article examines the process of generating group authorship of a play, the role and responsibilities of a practitioner in this process and the 'real life' consequences of creating applied theatre works that address issues of race, culture and identity in a contemporary Australian context.